2014
DOI: 10.1038/cddis.2014.152
|View full text |Cite
|
Sign up to set email alerts
|

Selective 14-3-3γ induction quenches p-β-catenin Ser37/Bax-enhanced cell death in cerebral cortical neurons during ischemia

Abstract: Ischemia-induced cell death is a major cause of disability or death after stroke. Identifying the key intrinsic protective mechanisms induced by ischemia is critical for the development of effective stroke treatment. Here, we reported that 14-3-3γ was a selective ischemia-inducible survival factor in cerebral cortical neurons reducing cell death by downregulating Bax depend direct 14-3-3γ/p-β-catenin Ser37 interactions in the nucleus. 14-3-3γ, but not other 14-3-3 isoforms, was upregulated in primary cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Western blot analysis and fluorescent cytoimmunostaining were performed as described previously [45]. Briefly, equal amounts of total proteins were subjected to mini-PAGE gel electrophoresis and transferred to NC membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis and fluorescent cytoimmunostaining were performed as described previously [45]. Briefly, equal amounts of total proteins were subjected to mini-PAGE gel electrophoresis and transferred to NC membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-four hours after cell seeding, interfering RNAs at 50 nM were transfected into HepG2 cells using Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) as previously reported [45]. Two days after siRNA trensfection, the cultures were subjected to PL treatment and the corresponding assays.…”
Section: Methodsmentioning
confidence: 99%
“…The pro-apoptotic activity of ASK1 is inhibited by interaction with 14-3-3 proteins. Moreover, 14-3-3 acts as a survival factor in oxygen-glucose deprivation-induced cell death [21]. They also demonstrated that knockout of 14-3-3 increases Bax expression, whereas overexpression of 14-3-3 decreases Bax expression [21].…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial observations that, after ischemia, BAX is upregulated in central neurons (Krajewski et al, 1995), and translocates to neuronal mitochondria (Cao et al, 2001), BAX has been observed to play a key role in multiple models of ischemia-induced neuronal death (Fan et al, 2012; Lai et al, 2014; Pei et al, 2014; Wang et al, 2011). In addition to BAX, BID has been implicated in neuronal death following OGD in vitro and HI in vivo (Plesnila et al, 2001), as well as in early cytochrome c release following HI (Yin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%